2019
DOI: 10.1016/j.molmet.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 modulates the supramammillary nucleus-lateral hypothalamic neurocircuit to control ingestive and motivated behavior in a sex divergent manner

Abstract: ObjectiveThe supramammillary nucleus (SuM) is nestled between the lateral hypothalamus (LH) and the ventral tegmental area (VTA). This neuroanatomical position is consistent with a potential role of this nucleus to regulate ingestive and motivated behavior. Here neuroanatomical, molecular, and behavior approaches are utilized to determine whether SuM contributes to ingestive and food-motivated behavior control.MethodsThrough the application of anterograde and retrograde neural tract tracing with novel designer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 51 publications
(85 reference statements)
4
22
0
Order By: Relevance
“…We show that ORX/MCH/TH‐negative DMH neurones innervate the SuMM, and also show the existence of a potentially dopaminergic SuM output to the DMH. Taken together, these data support the concept that the SuM is part of the brain's appetite control and/or motivational system and open avenues to further work characterising the functional circuitry involved in these behaviours.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…We show that ORX/MCH/TH‐negative DMH neurones innervate the SuMM, and also show the existence of a potentially dopaminergic SuM output to the DMH. Taken together, these data support the concept that the SuM is part of the brain's appetite control and/or motivational system and open avenues to further work characterising the functional circuitry involved in these behaviours.…”
Section: Discussionsupporting
confidence: 69%
“…We have previously shown that rat SuM neurones are sensitive to this hormone . Similarly, GLP‐1 levels increase in the rat before food access in a model of scheduled feeding of a standard diet, and motivation‐related brain nuclei are sensitive to analogues of this hormone when administered centrally …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Expression of supramammillary nucleus (SuM) GLP-1R is comparable with the expression in the LH and NAc, but lower than that found in the NTS (López-Ferreras et al, 2019 ). Activation of GLP-1R by infusion of Ex-4 (0.01 and 0.03 μg) into the SuM or AAV virus in male or female rats was found to be potently anorexigenic.…”
Section: Resultsmentioning
confidence: 80%